2010
DOI: 10.1038/onc.2010.165
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in myosin light-chain phosphorylation causes cytokinesis failure and multipolarity in cancer cells

Abstract: Cancer cells often have unstable genomes and increased centrosome and chromosome numbers, which play an important part of malignant transformation in the most recent models tumorigenesis. However, very little is known about divisional failures in cancer cells that may lead to chromosomal and centrosomal amplifications. We show here that cancer cells often failed at cytokinesis due to decreased phosphorylation of the myosin regulatory light chain (MLC), a key regulatory component of cortical contraction during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Consistently, the secondary hub enlargement defect in nos > H3T3D testes was also suppressed (Figure 7W). These findings are reminiscent of published studies in which expression of a phospho-mimic substrate can rescue the phenotypes of compromised kinase activity in cancer cells (Wu et al, 2010). Together, the opposite genetic interactions between haspin and the two H3 mutations on T3 further support the hypothesis that H3T3P needs to be tightly controlled for proper H3 inheritance and germline activity.…”
Section: Resultssupporting
confidence: 68%
“…Consistently, the secondary hub enlargement defect in nos > H3T3D testes was also suppressed (Figure 7W). These findings are reminiscent of published studies in which expression of a phospho-mimic substrate can rescue the phenotypes of compromised kinase activity in cancer cells (Wu et al, 2010). Together, the opposite genetic interactions between haspin and the two H3 mutations on T3 further support the hypothesis that H3T3P needs to be tightly controlled for proper H3 inheritance and germline activity.…”
Section: Resultssupporting
confidence: 68%
“…Increasing evidence suggests that myosins play essential roles in cases of cytokinesis failure [58], chromosomal and centrosomal amplification [59], multipolar spindle formation [55] and DNA microsatellite instability [36]. Identifying myosins' specific functions and clarifying their related mechanisms have become a prime focus in oncology.…”
Section: Effects Of Myosins On Genetic or Chromosomal Instabilitymentioning
confidence: 99%
“…Wu et al [59] found that cancer cells always failed at cytokinesis because of reduced phosphorylation of the myosin regulatory light chain (MLC). This limited MLC phosphorylation level was correlated with the overexpression of myosin phosphatase (MYPT1) and decreased expression of myosin light chain kinase (MLCK).…”
Section: Effects Of Myosins On Genetic or Chromosomal Instabilitymentioning
confidence: 99%
“…These results were somewhat expected, because disruption of MLC2 phosphorylation caused multipolar spindles and cytokinesis failure in cancer cells. 25 It was also reported that expression of unphosphorylated MLC2 in mammalian cells caused failure of cytokinesis. 26 Thus, our result suggested that MLC2 phosphorylation may positively affect polar body extrusion in mouse oocytes meiosis.…”
Section: Discussionmentioning
confidence: 99%